Hematological adaptations and detection of recombinant human erythropoietin combined with chronic hypoxia. Issue 2 (27th September 2020) - Bejder, Jacob; Breenfeldt Andersen, Andreas; Bonne, Thomas Christian; Linkis, Jesper; Olsen, Niels Vidiendal; Huertas, Jesús Rodríguez; Nordsborg, Nikolai Baastrup
Abstract: This study evaluated whether recombinant human erythropoietin (rhEpo) treatment combined with chronic hypoxia provided an additive erythropoietic response and whether the athlete biological passport (ABP) sensitivity improved with hypoxia. Two interventions were completed, each containing 4 weeks baseline, 4 weeks exposure at sea level or 2, 320 m of altitude, and 4 weeks follow‐up. Participants were randomly assigned to 20 IU·kg bw −1 rhEpo or placebo injections every second day for 3 weeks during the exposure period at sea level (rhEpo n = 25, placebo n = 9) or at altitude (rhEpo n = 12, placebo n = 27). Venous blood was analyzed weekly. Combining rhEpo and hypoxia induced larger changes compared with rhEpo or hypoxia alone for [Hb] ( p < 0.001 and p > 0.05, respectively), reticulocyte percentage ( p < 0.001), and OFF‐hr score ( p < 0.01 and p < 0.001, respectively). The most pronounced effect was observed for reticulocyte percentage with up to ~35% ( p < 0.001) and ~45% ( p < 0.001) higher levels compared with rhEpo or hypoxia only, respectively. The ABP sensitivity for the combined treatment was 54 and 35 percentage points higher for [Hb] ( p < 0.05) and reticulocyte percentage ( p < 0.05), respectively, but similar for OFF‐hr score, compared with rhEpo at sea level. Across any time point, [Hb] and OFF‐hr score combined identified 14 unique true‐positive participants (56%) at sea level and 12 unique true‐positive participants (100%) at altitude. However, a concurrent reduction in specificity existed at altitude. In conclusion, rhEpo treatment combined with hypoxic exposure provided an additive erythropoietic response compared with rhEpo or hypoxic exposure alone. Correspondingly, ABP was more sensitive to rhEpo at altitude than at sea level, but a compromised specificity existed with hypoxic exposure. Abstract : This study evaluated whether recombinant human erythropoietin treatment combined with chronic hypoxia provided an additive erythropoietic response and whether the athlete biological passport sensitivity improved with hypoxia.